2018
DOI: 10.1155/2018/8283648
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Progenitor Cells in Basic Biology and Regenerative Medicine

Abstract: Major cardiovascular events including myocardial infarction (MI) continue to dominate morbidity rates in the developed world. Although multiple device therapies and various pharmacological agents have been shown to improve patient care and reduce mortality rates, clinicians and researchers alike still lack a true panacea to regenerate damaged cardiac tissue. Over the previous two to three decades, cardiovascular stem cell therapies have held great promise. Several stem cell-based approaches have now been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…IPSC-derived CMs have also been shown to integrate into infarcted guinea pig heart, improving cardiac function and suppressing arrhythmias [ 13 ]. Human iPSC-derived cardiovascular progenitors have been successfully tested more recently in preclinical studies of canine and porcine MI models [ 14 ].…”
Section: Cardiac Generation Of Ipscsmentioning
confidence: 99%
“…IPSC-derived CMs have also been shown to integrate into infarcted guinea pig heart, improving cardiac function and suppressing arrhythmias [ 13 ]. Human iPSC-derived cardiovascular progenitors have been successfully tested more recently in preclinical studies of canine and porcine MI models [ 14 ].…”
Section: Cardiac Generation Of Ipscsmentioning
confidence: 99%
“…However, there is still no reliable therapy for acute cardiac conditions like myocardial infarction (MI), which account for nearly half of all cardiovascular deaths in the industrialized world [1,2]. Regenerative medicine-based strategies for infarcted myocardium have shown promise in preclinical animal models as well as early clinical trials [3]. Whilst these have demonstrated some physiological improvements in ventricular function, they were associated with very low cell retention after some weeks, suggesting a paracrine effect of transplanted cells rather than functional integration within the damaged tissue [4].…”
Section: Cardiac Regeneration-a Problem To Solve or A Solution With Pmentioning
confidence: 99%
“…Several studies have demonstrated that the cells generated from CPCs, particularly cardiomyocytes, display an immature phenotype similar to that of embryonic cardiac cells [3]. However, when the CPCs are transplanted into a host environment, the differentiated cells reach a more advanced maturity, such as greater organisation of sarcomeres and formation of gap junctions (in the case of cardiomyocytes) and development of tubular-like structures (for smooth muscle and endothelial cells) [11,24,27,28].…”
Section: Tissue Engineering With Cpcs and Cpc-derived Cardiomyocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, also CPCs-derived exosomes are able to exert, once released in the extracellular microenvironment, positive therapeutic effects through multiple mechanisms interacting with different target cells, such as endothelial cells and cardiomyocytes [72][73][74] . Overall, despite all these encouraging results many critical issues, including the challenges of electrical coupling, undetermined mechanism aspects and, above all, the long term engraftment and survival of injected cells, should be addressed before CPCs could be considered as a strong therapeutic tool for regenerative medicine applications [75] .…”
Section: Adult Cpcsmentioning
confidence: 99%